Improvement of assessment program to classify the visual field grade in physical disability using Humphrey Field Analyzer - Usui, Masahiko; Harasawa, Kayoko; Endo, Nariyoshi; Kodera, Hisako; Kunugita, Sayaka (JAPANESE ORTHOPTIC JOURNAL, 1999)
We reported the trial assessment program to classify the visual field grade in physical disability using with Humphery Field Analyzer 630 (HFA) last year. The classification results from Goldmann Perimeter (GP) and HFA were different in 11 of 25 cases (44.0%) in the program. So, this time, we wanted to improve the program and changed 8 test points from 10 degrees circle to 11 degrees circle. Subjects were 49 eyes of 26 cases which consisted mainly of retinitis pigmentosa. The cases were tested for visual field using both our original program with HFA and GP in order to determine the classification. The average testing time of the new program for peripheral with 10dB was 4 minutes and 37 seconds, that of the program for central with 20dB was 1 minute and 58 seconds, and the average total was 6 minutes and 35 seconds. In this program, the classification results using GP and HFA were coincident in 22 of 26 cases (84.6%), much more than the former report. This new program may be recommended as a more useful method to classify the assessment grade.